2016
DOI: 10.1536/ihj.16-026
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Variability and Reduction in Blood Pressure After a 3-Month Cardiac Rehabilitation Program in Patients With Cardiovascular Disease

Abstract: SummaryVisit-to-visit variability (VVV) in blood pressure (BP) has been shown to be a predictor of cardiovascular events. It is unknown whether CR can improve VVV in BP as well as reducing BP. We enrolled 84 patients who had cardiovascular disease (CVD) and participated in a 3-month CR program. We measured systolic and diastolic BP (SBP and DBP), pulse pressure (PP), and heart rate (HR) before exercise training at each visit and determined VVV in BP or HR expressed as the standard deviation of the average BP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Patients who had uncontrolled BP at baseline and who did not change their antihypertensive drugs throughout the study period showed a significant reduction of both SBP and DBP after 3 months. Patients who did not change their antihypertensive drugs were divided into high and low VVV in the SBP groups according to the average value of VVV in SBP or DBP and found that VVV in SBP and DBP in the 1st month was significantly decreased than the 3rd month in both groups [29]. Our study revealed considerable amount of the participants (26.6% CI: 22.5–31.1) had insufficient (sedentary) physical activity level, and 20.4% (16.7–24.6) reported as moderately active.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who had uncontrolled BP at baseline and who did not change their antihypertensive drugs throughout the study period showed a significant reduction of both SBP and DBP after 3 months. Patients who did not change their antihypertensive drugs were divided into high and low VVV in the SBP groups according to the average value of VVV in SBP or DBP and found that VVV in SBP and DBP in the 1st month was significantly decreased than the 3rd month in both groups [29]. Our study revealed considerable amount of the participants (26.6% CI: 22.5–31.1) had insufficient (sedentary) physical activity level, and 20.4% (16.7–24.6) reported as moderately active.…”
Section: Resultsmentioning
confidence: 99%
“…We have studied CR for more than eight years and reported some beneficial effects in patients with cardiovascular diseases (CVD) [12][13][14][15][16][17]. We previously reported that a CR program significantly reduced blood pressure (BP) and visit-to-visit variability in BP, and patients with mild to moderate chronic kidney disease (CKD) who participated in our CR program showed an increase in their estimated glomerular filtration rate (eGFR) [14,15]. We also reported that long-term CR in elderly CVD outpatients helped to maintain the anaerobic threshold (AT), left ventricular EF (LVEF), plasma levels of brain natriuretic peptide (BNP) and eGFR for 5 years [16].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive cardiac rehabilitation (CR) has been shown to improve cardiac function and prognosis in patients with cardiovascular disease (CVD) [1] , [2] . Recently, we reported that a 3-month CR program significantly decreased blood pressure (BP) [3] and improved atherosclerosis and sympathetic nerve as assessed by 3 simple non-invasive tests: BP and severity of atherosclerosis [arterial velocity pulse index (AVI) and arterial pressure volume index (API)] were determined using PASESA® (AVE-1500, Shisei Datum, Tokyo, Japan), an index of total autonomic nerve activity and a coefficient of variation of the R-R interval (CVRR) were determined using eHEART® (Parama-Tec, Fukuoka, Japan), and absolute and relative differences in BP between arms, pressure rate product (PRP), mean total peripheral resistance index (TPR), stroke volume (SV), and cardiac index (CI) were determined using nico® (Parama-Tec, Fukuoka, Japan) [4] . These 3 easy-to-use devices, PASESA® [5] , nico PS-501® (North Parama Inc., Tokyo, Japan) [6] and eHEART® [7] , are currently available for clinical use in Japan.…”
Section: Introductionmentioning
confidence: 99%